A high-elongation two-component polyurethane structural adhesive suitable for bonding power batteries and a preparation method thereof

By introducing the "rotaxane" structure into the two-component polyurethane adhesive, the problem in the existing technology that it is difficult to maintain the body strength and bonding strength when the elongation at break is increased is solved, and high elongation and excellent bonding properties are achieved. Suitable for bonding power battery structures.

CN115785886BActive Publication Date: 2025-01-24HANGZHOU ZHIJIANG SILICONE CHEM +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211484259.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-24
Publication Date
2025-01-24
Estimated Expiration
2042-11-24

AI Technical Summary

Technical Problem

While existing two-component polyurethane adhesives are difficult to maintain body strength and bond strength while increasing the elongation of break, and traditional methods such as adding plasticizers or reducing crosslinking density will affect the construction performance of the product.

Method used

Introducing a unique "rotaxane" structure, by introducing a cyclic structure, such as cyclodextrin, into the polyether polyol polymer chain, and reacting with the isocyanate curing agent component to form movable chain segments to increase the elongation at break .

Benefits of technology

Without sacrificing the body strength and bonding strength, the elongation at break of the adhesive is significantly improved, which is especially suitable for structural bonding in power batteries. The preparation method has easily available raw materials, simple operation, mild conditions, and has excellent properties. Industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003962273900000111
    Figure BDA0003962273900000111
  • Figure HDA0003962273910000011
    Figure HDA0003962273910000011
Patent Text Reader

Abstract

The invention provides a high-elongation two-component polyurethane structural adhesive suitable for bonding power batteries, comprising an A component and a B component in a volume ratio of (0.8-1.2):1; the A component comprises: 20-40 parts by weight of modified castor oil; 1-10 parts by weight of a small molecule diol chain extender; 1-10 parts by weight of a "rotaxane" structure; 40-80 parts by weight of an organic nitrogen-phosphorus polymer flame-retardant filler; 0.5-5 parts by weight of a white carbon black thixotropic agent; 0.3-3 parts by weight of a silane coupling agent; 0.01-1 parts by weight of a metal catalyst; 0.1-2 parts by weight of a blue color paste; the B component comprises: 20-40 parts by weight of a polymer polyisocyanate; 5-20 parts by weight of a polyether diol; 40-80 parts by weight of an organic nitrogen-phosphorus polymer flame-retardant filler; 0.5-3 parts by weight of a 4A molecular sieve water absorbent; 0.5-5 parts by weight of a white carbon black thixotropic agent; and 0.1-2 parts by weight of a yellow color paste. This two-component polyurethane structural adhesive introduces a unique "rotaxane" structure, which provides a higher elongation at break while meeting the requirements of structural bonding and bulk strength, and is particularly suitable for structural bonding in power batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesives, and more specifically to a high-elongation two-component polyurethane structural adhesive suitable for bonding power batteries and a preparation method thereof. Background Art

[0002] Currently in the field of power batteries, customers have increasingly stringent demands for two-component polyurethane structural adhesives; not only do they require high body strength and strong substrate adhesion, but they also require the cured adhesive to have good tensile properties and high elongation at break.

[0003] At present, in the field of two-component polyurethane adhesives, there are three main methods to improve the elongation at break. The first is to add plasticizers; the second is to reduce the crosslinking density of the resin, that is, to use more bifunctional polyols to replace multifunctional polyol resins; the third is to increase the molecular weight of the polyol and increase the proportion of soft segments in the system. However, all three methods will soften the cured glue, sacrificing the bulk strength and reducing the bonding ability to the substrate to a certain extent. Specifically, the purpose of adding plasticizers is to destroy the hydrogen bonds between the molecular chains and to have a certain disentanglement effect on the polymer chains, which will greatly reduce the strength of the adhesive; reducing the functionality of the polyol will reduce the crosslinking density of the overall three-dimensional network structure, which will not only make the adhesive softer, but also reduce the glass transition temperature of the product, making the product's high temperature resistance weakened; although increasing the molecular weight of the polyol can improve the elongation at break while ensuring the bulk strength, the increase in molecular weight will lead to a sharp increase in the viscosity of the system, which will seriously affect the construction performance of the product. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a high-elongation two-component polyurethane structural adhesive suitable for power battery bonding and a preparation method thereof. The high-elongation two-component polyurethane structural adhesive suitable for power battery bonding provided by the present invention can improve the elongation at break of the adhesive without sacrificing the body strength and bonding strength.

[0005] The present invention provides a high-elongation two-component polyurethane structural adhesive suitable for bonding power batteries, comprising component A and component B in a volume ratio of (0.8-1.2):1;

[0006] The A component comprises:

[0007] 20-40 parts by weight of modified castor oil;

[0008] 1 to 10 parts by weight of a small molecule diol chain extender;

[0009] 1 to 10 parts by weight of "rotaxane" structure;

[0010] 40-80 parts by weight of organic nitrogen and phosphorus polymer flame retardant filler;

[0011] 0.5-5 parts by weight of white carbon black thixotropic agent;

[0012] 0.3 to 3 parts by weight of silane coupling agent;

[0013] 0.01 to 1 parts by weight of a metal catalyst;

[0014] 0.1-2 parts by weight of blue color paste;

[0015] The B component includes:

[0016] 20-40 parts by weight of polymer polyisocyanate;

[0017] 5 to 20 parts by weight of polyether diol;

[0018] 40-80 parts by weight of organic nitrogen and phosphorus polymer flame retardant filler;

[0019] 0.5 to 3 parts by weight of 4A molecular sieve water absorbent;

[0020] 0.5-5 parts by weight of white carbon black thixotropic agent;

[0021] 0.1 to 2 parts by weight of yellow color paste.

[0022] Preferably, the A component consists of the following components:

[0023] 29-33 parts by weight of modified castor oil;

[0024] 5 to 7 parts by weight of a small molecule diol chain extender;

[0025] 2 to 6 parts by weight of "rotaxane" structure;

[0026] 50-60 parts by weight of organic nitrogen and phosphorus polymer flame retardant filler;

[0027] 1 to 3 parts by weight of white carbon black thixotropic agent;

[0028] Silane coupling agent 0.5-1.5 parts by weight;

[0029] 0.05-0.15 parts by weight of metal catalyst;

[0030] 0.5-1.5 parts by weight of blue color paste.

[0031] Preferably, the B component consists of the following components:

[0032] 25-35 parts by weight of polymer polyisocyanate;

[0033] 8 to 12 parts by weight of polyether diol;

[0034] 50-60 parts by weight of organic nitrogen and phosphorus polymer flame retardant filler;

[0035] 1.5-2.5 parts by weight of 4A molecular sieve water absorbent;

[0036] 1 to 3 parts by weight of white carbon black thixotropic agent;

[0037] 0.5-1.5 parts by weight of yellow color paste.

[0038] Preferably, the preparation method of the "rotaxane" structure is specifically as follows:

[0039] Cyclodextrin and polyether diol are reacted in water at a ratio of molar equivalent (1-10):1, and then the water is removed and finally dried to obtain a "rotaxane" structure.

[0040] Preferably, the cyclodextrin is selected from one or more of α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin;

[0041] The average molecular weight of the polyether diol is 400-12000.

[0042] Preferably, the reaction temperature is 20°C to 30°C, the stirring speed is 100rpm to 300rpm, and the reaction time is 1h to 4h.

[0043] Preferably, the method for removing water is rotary evaporation; the vacuum degree of the rotary evaporation is ≤-0.09MPa, the temperature is 50°C to 70°C, and the rotation speed is 30rpm to 50rpm.

[0044] Preferably, the drying method is vacuum drying; the vacuum drying temperature is 70°C to 90°C, the vacuum degree is ≤-0.09MPa, and the time is 10h to 15h.

[0045] The present invention also provides a method for preparing the high-elongation two-component polyurethane structural adhesive suitable for bonding power batteries as described in the above technical solution, comprising the following steps:

[0046] a) heating the modified castor oil, the small molecule diol chain extender, the "rotaxane" structure, the organic nitrogen and phosphorus polymer flame retardant filler, the white carbon black thixotropic agent and the silane coupling agent to 110° C. to 130° C. under stirring, dehydrating for 1.5 h to 2.5 h under vacuum ≤-0.09 MPa, then cooling by ≤50° C., adding the metal catalyst and the blue color paste, and continuing to stir for 0.5 h to 1 h under vacuum ≤-0.09 MPa to obtain component A;

[0047] b) stirring the polymer polyisocyanate and the polyether diol at 20° C. to 30° C. and evacuating to ≤-0.09 MPa for reaction for 1 h to 3 h, then adding organic nitrogen phosphorus polymer flame retardant filler, 4A molecular sieve dehydrating agent and white carbon black thixotropic agent, and then adding yellow color paste, stirring at 20° C. to 30° C. and evacuating to ≤-0.09 MPa for reaction for 0.5 h to 1.5 h to obtain component B;

[0048] c) mixing the above-mentioned component A and component B in a volume ratio of (0.8-1.2):1 to obtain a high-elongation two-component polyurethane structural adhesive suitable for bonding power batteries;

[0049] There is no restriction on the order of step a) and step b).

[0050] Preferably, before the organic nitrogen and phosphorus polymer flame retardant filler, 4A molecular sieve dehydrating agent and white carbon black thixotropic agent are added in step b), the method further comprises:

[0051] The organic nitrogen and phosphorus polymer flame retardant filler, 4A molecular sieve water absorbent and white carbon black thixotropic agent are dried and dehydrated in a drying room at 90°C to 110°C for 20h to 30h.

[0052] The invention provides a high-elongation two-component polyurethane structural adhesive suitable for bonding power batteries, comprising an A component and a B component in a volume ratio of (0.8-1.2):1; the A component comprises: 20-40 parts by weight of modified castor oil; 1-10 parts by weight of a small molecule diol chain extender; 1-10 parts by weight of a "rotaxane" structure; 40-80 parts by weight of an organic nitrogen-phosphorus polymer flame-retardant filler; 0.5-5 parts by weight of a white carbon black thixotropic agent; 0.3-3 parts by weight of a silane coupling agent; 0.01-1 parts by weight of a metal catalyst; 0.1-2 parts by weight of a blue color paste; the B component comprises: 20-40 parts by weight of a polymer polyisocyanate; 5-20 parts by weight of a polyether diol; 40-80 parts by weight of an organic nitrogen-phosphorus polymer flame-retardant filler; 0.5-3 parts by weight of a 4A molecular sieve water absorbent; 0.5-5 parts by weight of a white carbon black thixotropic agent; and 0.1-2 parts by weight of a yellow color paste. Compared with the prior art, the two-component polyurethane structural adhesive provided by the present invention introduces a unique "rotaxane" structure, avoids the use of traditional plasticizers or reduces the crosslinking density, and cooperates with other specific components with specific contents to achieve better overall interaction. The product provides a higher elongation at break while meeting the requirements of structural bonding and bulk strength, and is particularly suitable for structural bonding in power batteries. Experimental results show that the tensile shear strength of the two-component polyurethane structural adhesive provided by the present invention is 10.7-10.9MPa (25°C, 7d), the bulk tensile strength is 10.9-11.4MPa (25°C, 7d), the elongation at break is 35-63% (25°C, 7d), and the elastic modulus is 670-700MPa (25°C, 7d).

[0053] In addition, the preparation method provided by the present invention has readily available raw materials, simple operation, mild conditions, and has excellent industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 Schematic diagram of the principle of improving the elongation at break for the "rotaxane" structure. DETAILED DESCRIPTION

[0055] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0056] The present invention provides a high-elongation two-component polyurethane structural adhesive suitable for bonding power batteries, comprising a component A and a component B in a volume ratio of (0.8-1.2):1;

[0057] The A component includes:

[0058] 20-40 parts by weight of modified castor oil;

[0059] 1 to 10 parts by weight of a small molecule diol chain extender;

[0060] 1 to 10 parts by weight of "rotaxane" structure;

[0061] 40-80 parts by weight of organic nitrogen and phosphorus polymer flame retardant filler;

[0062] 0.5-5 parts by weight of white carbon black thixotropic agent;

[0063] 0.3 to 3 parts by weight of silane coupling agent;

[0064] 0.01 to 1 parts by weight of a metal catalyst;

[0065] 0.1-2 parts by weight of blue color paste;

[0066] The B component includes:

[0067] 20-40 parts by weight of polymer polyisocyanate;

[0068] 5 to 20 parts by weight of polyether diol;

[0069] 40-80 parts by weight of organic nitrogen and phosphorus polymer flame retardant filler;

[0070] 0.5 to 3 parts by weight of 4A molecular sieve water absorbent;

[0071] 0.5-5 parts by weight of white carbon black thixotropic agent;

[0072] 0.1 to 2 parts by weight of yellow color paste.

[0073] In the present invention, the high elongation two-component polyurethane structural adhesive suitable for power battery bonding includes component A and component B in a volume ratio of (0.8-1.2):1, preferably composed of component A and component B in a volume ratio of (0.8-1.2):1, and more preferably composed of component A and component B in a volume ratio of 1:1.

[0074] In the present invention, the A component comprises:

[0075] 20-40 parts by weight of modified castor oil;

[0076] 1 to 10 parts by weight of a small molecule diol chain extender;

[0077] 1 to 10 parts by weight of "rotaxane" structure;

[0078] 40-80 parts by weight of organic nitrogen and phosphorus polymer flame retardant filler;

[0079] 0.5-5 parts by weight of white carbon black thixotropic agent;

[0080] 0.3 to 3 parts by weight of silane coupling agent;

[0081] 0.01 to 1 parts by weight of a metal catalyst;

[0082] 0.1-2 parts by weight of blue color paste;

[0083] It is preferably composed of the following components:

[0084] 29-33 parts by weight of modified castor oil;

[0085] 5 to 7 parts by weight of a small molecule diol chain extender;

[0086] 2 to 6 parts by weight of "rotaxane" structure;

[0087] 50-60 parts by weight of organic nitrogen and phosphorus polymer flame retardant filler;

[0088] 1 to 3 parts by weight of white carbon black thixotropic agent;

[0089] Silane coupling agent 0.5-1.5 parts by weight;

[0090] 0.05-0.15 parts by weight of metal catalyst;

[0091] 0.5-1.5 parts by weight of blue color paste.

[0092] In the present invention, the B component comprises:

[0093] 20-40 parts by weight of polymer polyisocyanate;

[0094] 5 to 20 parts by weight of polyether diol;

[0095] 40-80 parts by weight of organic nitrogen and phosphorus polymer flame retardant filler;

[0096] 0.5 to 3 parts by weight of 4A molecular sieve water absorbent;

[0097] 0.5-5 parts by weight of white carbon black thixotropic agent;

[0098] 0.1-2 parts by weight of yellow color paste;

[0099] It is preferably composed of the following components:

[0100] 25-35 parts by weight of polymer polyisocyanate;

[0101] 8 to 12 parts by weight of polyether diol;

[0102] 50-60 parts by weight of organic nitrogen and phosphorus polymer flame retardant filler;

[0103] 1.5-2.5 parts by weight of 4A molecular sieve water absorbent;

[0104] 1 to 3 parts by weight of white carbon black thixotropic agent;

[0105] 0.5-1.5 parts by weight of yellow color paste.

[0106] The present invention has no special restrictions on the sources of the modified castor oil, small molecule diol chain extender, organic nitrogen and phosphorus polymer flame retardant filler, white carbon black thixotropic agent, silane coupling agent, metal catalyst, blue color paste, polymer polyisocyanate, polyether diol, 4A molecular sieve water absorbent, and yellow color paste, and commercially available products well known to those skilled in the art can be used.

[0107] In the present invention, the preparation method of the "rotaxane" structure is preferably as follows:

[0108] Cyclodextrin and polyether diol are reacted in water at a ratio of molar equivalent (1-10):1, and then the water is removed and finally dried to obtain a "rotaxane" structure.

[0109] In the present invention, the cyclodextrin is preferably selected from one or more of α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin, and β-cyclodextrin is more preferred; the average molecular weight of the polyether diol is preferably 400 to 12000, and more preferably 1000 to 3000. The present invention has no particular restrictions on the sources of the cyclodextrin and the polyether diol, and commercially available products known to those skilled in the art can be used.

[0110] In the present invention, the reaction temperature is preferably 20° C. to 30° C., the stirring speed is preferably 100 rpm to 300 rpm, more preferably 200 rpm, and the reaction time is preferably 1 h to 4 h, more preferably 2 h to 3 h.

[0111] In the present invention, the method for removing water is preferably rotary evaporation, using a rotary evaporator well known to those skilled in the art; the vacuum degree of the rotary evaporation is preferably ≤-0.09MPa, the temperature is preferably 50°C to 70°C, more preferably 60°C, and the rotation speed is preferably 30rpm to 50rpm, more preferably 40rpm.

[0112] In the present invention, the drying method is preferably vacuum drying, and a vacuum drying oven familiar to those skilled in the art can be used; the vacuum drying temperature is preferably 70°C to 90°C, more preferably 80°C, the vacuum degree is preferably ≤-0.09MPa, and the time is preferably 10h to 15h, more preferably 12h to 13h.

[0113] The present invention aims at the technical problem of improving the elongation at break of an adhesive without sacrificing bulk strength and bonding strength. The above-mentioned "rotaxane" structure is introduced into the formula, and a method for introducing the mechanical interlocking structure "rotaxane" into a polyurethane skeleton is developed, so as to achieve the improvement of the elongation at break of the cured adhesive while maintaining high bulk strength. The so-called "rotaxane" structure refers to the introduction of multiple cyclic structures such as cyclodextrin on the polymer chain of a polyether polyol, and these cyclic structures can further react with an isocyanate curing agent component. The advantage of introducing such a structure is that when external force is applied to the polyurethane skeleton, these rings on the polymer chain can slip, and this process can absorb a large amount of energy and give the polyurethane skeleton sufficient deformation ability, thereby greatly improving the elongation at break of the product.

[0114] In the present invention, the principle diagram of the "rotaxane" structure to improve the elongation at break is shown in Figure 1 shown.

[0115] The present invention also provides a method for preparing the high-elongation two-component polyurethane structural adhesive suitable for bonding power batteries as described in the above technical solution, comprising the following steps:

[0116] a) heating the modified castor oil, the small molecule diol chain extender, the "rotaxane" structure, the organic nitrogen and phosphorus polymer flame retardant filler, the white carbon black thixotropic agent and the silane coupling agent to 110° C. to 130° C. under stirring, dehydrating for 1.5 h to 2.5 h under vacuum ≤-0.09 MPa, then cooling by ≤50° C., adding the metal catalyst and the blue color paste, and continuing to stir for 0.5 h to 1 h under vacuum ≤-0.09 MPa to obtain component A;

[0117] b) stirring the polymer polyisocyanate and the polyether diol at 20° C. to 30° C. and evacuating to ≤-0.09 MPa for reaction for 1 h to 3 h, then adding organic nitrogen phosphorus polymer flame retardant filler, 4A molecular sieve dehydrating agent and white carbon black thixotropic agent, and then adding yellow color paste, stirring at 20° C. to 30° C. and evacuating to ≤-0.09 MPa for reaction for 0.5 h to 1.5 h to obtain component B;

[0118] c) mixing the above-mentioned component A and component B in a volume ratio of (0.8-1.2):1 to obtain a high-elongation two-component polyurethane structural adhesive suitable for bonding power batteries;

[0119] There is no restriction on the order of step a) and step b).

[0120] In the present invention, before the organic nitrogen and phosphorus polymer flame retardant filler, 4A molecular sieve dehydrating agent and white carbon black thixotropic agent are added, it is preferred that the following be further included:

[0121] Dry and dehydrate the organic nitrogen and phosphorus polymer flame retardant filler, 4A molecular sieve water absorbent and white carbon black thixotropic agent in a drying room at 90°C to 110°C for 20h to 30h;

[0122] More preferably:

[0123] The organic nitrogen and phosphorus polymer flame retardant filler, 4A molecular sieve water absorbent and white carbon black thixotropic agent were dried and dehydrated in a drying room at 100° C. for 24 hours.

[0124] The preparation method provided by the invention has readily available raw materials, simple operation, mild conditions and has excellent industrial application prospects.

[0125] Regarding the technical difficulty of how to improve the elongation at break, the traditional view is that it must be achieved by softening the glue. After all, for elastomers, toughness and strength are often incompatible. On this basis, people have previously considered weakening the intermolecular interaction by adding plasticizers or reducing the crosslinking density, thereby softening the glue to achieve the toughness of the glue. However, the present invention, by adding movable segments, can absorb energy through intermolecular slippage under the action of external forces, and provide the polymer skeleton with excellent deformability, which can greatly improve the deformation ability of the glue without destroying the intramolecular interaction, and ultimately achieve the improvement of the elongation at break without sacrificing the bulk strength and hardness. Therefore, the present invention achieves the technical effect of improving the elongation at break of the adhesive without sacrificing the bulk strength and bonding strength.

[0126] The invention provides a high-elongation two-component polyurethane structural adhesive suitable for bonding power batteries, comprising an A component and a B component in a volume ratio of (0.8-1.2):1; the A component comprises: 20-40 parts by weight of modified castor oil; 1-10 parts by weight of a small molecule diol chain extender; 1-10 parts by weight of a "rotaxane" structure; 40-80 parts by weight of an organic nitrogen-phosphorus polymer flame-retardant filler; 0.5-5 parts by weight of a white carbon black thixotropic agent; 0.3-3 parts by weight of a silane coupling agent; 0.01-1 parts by weight of a metal catalyst; 0.1-2 parts by weight of a blue color paste; the B component comprises: 20-40 parts by weight of a polymer polyisocyanate; 5-20 parts by weight of a polyether diol; 40-80 parts by weight of an organic nitrogen-phosphorus polymer flame-retardant filler; 0.5-3 parts by weight of a 4A molecular sieve water absorbent; 0.5-5 parts by weight of a white carbon black thixotropic agent; and 0.1-2 parts by weight of a yellow color paste. Compared with the prior art, the two-component polyurethane structural adhesive provided by the present invention introduces a unique "rotaxane" structure, avoids the use of traditional plasticizers or reduces the crosslinking density, and cooperates with other specific components with specific contents to achieve overall good interaction. The product provides a higher elongation at break while meeting the requirements of structural bonding and bulk strength, and is particularly suitable for structural bonding in power batteries. Experimental results show that the tensile shear strength of the two-component polyurethane structural adhesive provided by the present invention is 10.7-10.9MPa (25°C, 7d), the bulk tensile strength is 10.9-11.4MPa (25°C, 7d), the elongation at break is 35-63% (25°C, 7d), and the elastic modulus is 670-700MPa (25°C, 7d).

[0127] In addition, the preparation method provided by the present invention has readily available raw materials, simple operation, mild conditions, and has excellent industrial application prospects.

[0128] In order to further illustrate the present invention, the following examples are used to provide a detailed description. The raw materials used in the following examples of the present invention are all commercially available products; wherein the "rotaxane" structure is obtained according to the following preparation method:

[0129] In a 500mL single-necked flask, 113g of β-cyclodextrin was dispersed in 200mL of water, and then 200g of polyether diol (molecular weight of 2000, brand Yantai Wanhua C2020) was added, and the mixture was stirred at 25°C and 200rpm for 2h; after the reaction was completed, the water in the flask was removed by a rotary evaporator, and the vacuum degree was set to ≤-0.09MPa, the temperature was 60°C, and the speed was 40rpm; finally, the residual liquid was placed in a vacuum drying oven and dried at 80°C and a vacuum degree of ≤-0.09MPa for 12h to obtain a white powdery "rotaxane" structure.

[0130] The performance testing method adopted by the present invention is as follows:

[0131] Tensile shear strength: GB / T 7124-2008 Determination of tensile shear strength of adhesives (rigid material to rigid material), the test substrate is 3003Al, the bonding thickness is 0.2mm;

[0132] Bulk tensile strength, elongation at break: GB / T 528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber, I-type spline, thickness of 2mm, tensile speed of 100mm / min;

[0133] Elastic modulus: The test was carried out in the tensile mode of the DMA equipment, with a specimen thickness of 1 mm, a scanning frequency of 1 Hz, and a heating rate of 1 °C / min in the heating mode.

[0134] Example 1

[0135] Component A: 33 parts by weight of Ito modified castor oil H-368, 6 parts by weight of chain extender EHD, 2 parts by weight of rotaxane structure, 55 parts by weight of Foshan Jinge JAZ-004 flame retardant powder, 2 parts by weight of CABOT TS720 white carbon black, 1 part by weight of KH-560 silane coupling agent, 0.1 parts by weight of American Vantrus Coscat-83 catalyst, and 1 part by weight of Bomeishi blue color paste;

[0136] Component B: 30 parts by weight of Yantai Wanhua PM-200 polymer polyisocyanate, 10 parts by weight of Yantai Wanhua C2020 polyether diol, 55 parts by weight of Foshan Jinge JAZ-004 flame retardant powder, 2 parts by weight of 4A molecular sieve, 2 parts by weight of CABOT TS720 white carbon black, and 1 part by weight of Bomax yellow color paste.

[0137] Example 2

[0138] Component A: 31 parts by weight of Ito modified castor oil H-368, 6 parts by weight of chain extender EHD, 4 parts by weight of rotaxane structure, 55 parts by weight of Foshan Jinge JAZ-004 flame retardant powder, 2 parts by weight of CABOT TS720 white carbon black, 1 part by weight of KH-560 silane coupling agent, 0.1 parts by weight of American Vantrus Coscat-83 catalyst, and 1 part by weight of Bomeishi blue color paste;

[0139] Component B: 30 parts by weight of Yantai Wanhua PM-200 polymer polyisocyanate, 10 parts by weight of Yantai Wanhua C2020 polyether diol, 55 parts by weight of Foshan Jinge JAZ-004 flame retardant powder, 2 parts by weight of 4A molecular sieve, 2 parts by weight of CABOT TS720 white carbon black, and 1 part by weight of Bomax yellow color paste.

[0140] Example 3

[0141] Component A: 29 parts by weight of Ito modified castor oil H-368, 6 parts by weight of chain extender EHD, 6 parts by weight of rotaxane structure, 55 parts by weight of Foshan Jinge JAZ-004 flame retardant powder, 2 parts by weight of CABOT TS720 white carbon black, 1 part by weight of KH-560 silane coupling agent, 0.1 parts by weight of American Vantrus Coscat-83 catalyst, and 1 part by weight of Bomeishi blue color paste;

[0142] Component B: 30 parts by weight of Yantai Wanhua PM-200 polymer polyisocyanate, 10 parts by weight of Yantai Wanhua C2020 polyether diol, 55 parts by weight of Foshan Jinge JAZ-004 flame retardant powder, 2 parts by weight of 4A molecular sieve, 2 parts by weight of CABOT TS720 white carbon black, and 1 part by weight of Bomax yellow color paste.

[0143] Comparative Example 1

[0144] Component A: 35 parts by weight of Ito modified castor oil H-368, 6 parts by weight of chain extender EHD, 55 parts by weight of Foshan Jinge JAZ-004 flame retardant powder, 2 parts by weight of CABOT TS720 white carbon black, 1 part by weight of KH-560 silane coupling agent, 0.1 parts by weight of American Vantrus Coscat-83 catalyst, and 1 part by weight of Bomeishi blue color paste;

[0145] Component B: 30 parts by weight of Yantai Wanhua PM-200 polymer polyisocyanate, 10 parts by weight of Yantai Wanhua C2020 polyether diol, 55 parts by weight of Foshan Jinge JAZ-004 flame retardant powder, 2 parts by weight of 4A molecular sieve, 2 parts by weight of CABOT TS720 white carbon black, and 1 part by weight of Bomax yellow color paste.

[0146] Comparative Example 2

[0147] Component A: 35 parts by weight of Ito modified castor oil H-368, 6 parts by weight of chain extender EHD, 55 parts by weight of Foshan Jinge JAZ-004 flame retardant powder, 2 parts by weight of CABOT TS720 white carbon black, 1 part by weight of KH-560 silane coupling agent, 0.1 parts by weight of American Vantrus Coscat-83 catalyst, and 1 part by weight of Bomeishi blue color paste;

[0148] Component B: 30 parts by weight of Yantai Wanhua PM-200 polymer polyisocyanate, 10 parts by weight of Yantai Wanhua C2020 polyether diol, 45 parts by weight of Foshan Jinge JAZ-004 flame retardant powder, 10 parts by weight of DINP plasticizer, 2 parts by weight of 4A molecular sieve, 2 parts by weight of CABOT TS720 white carbon black, and 1 part by weight of Bomax yellow color paste.

[0149] Comparative Example 3

[0150] Component A: 25 parts by weight of Ito modified castor oil H-368, 10 parts by weight of Vantellus D-290 difunctional modified castor oil, 6 parts by weight of chain extender EHD, 55 parts by weight of Foshan Jinge JAZ-004 flame retardant powder, 2 parts by weight of CABOT TS720 white carbon black, 1 part by weight of KH-560 silane coupling agent, 0.1 parts by weight of American Vantellus Coscat-83 catalyst, and 1 part by weight of Bomeishi blue color paste;

[0151] Component B: 30 parts by weight of Yantai Wanhua PM-200 polymer polyisocyanate, 10 parts by weight of Yantai Wanhua C2020 polyether diol, 55 parts by weight of Foshan Jinge JAZ-004 flame retardant powder, 2 parts by weight of 4A molecular sieve, 2 parts by weight of CABOT TS720 white carbon black, and 1 part by weight of Bomax yellow color paste.

[0152] The component selection and proportions of Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 1.

[0153] Table 1 Component selection and ratio data table of Examples 1 to 3 and Comparative Examples 1 to 3

[0154]

[0155] The preparation method of the two-component polyurethane structural adhesive involved in the above test is as follows:

[0156] (1) The modified castor oil, small molecule diol chain extender, "rotaxane" structure, organic nitrogen and phosphorus polymer flame retardant filler, white carbon black thixotropic agent and silane coupling agent are heated to 120° C. under stirring, evacuated to -0.09 MPa for dehydration for 2 h, then cooled to below 50° C., a metal catalyst and a blue color paste are added, and the mixture is evacuated to below -0.09 MPa and stirred for 45 min to obtain component A.

[0157] (2) First, the organic nitrogen and phosphorus polymer flame retardant filler, 4A molecular sieve desiccant and white carbon black thixotropic agent are dried and dehydrated in a drying oven at 100°C for 24 hours and set aside; the polymer polyisocyanate and polyether diol are stirred at room temperature and evacuated to -0.09 MPa for reaction for 2 hours, and then the organic nitrogen and phosphorus polymer flame retardant filler, 4A molecular sieve desiccant and white carbon black thixotropic agent that have been dried in advance are added, and then the yellow color paste is added, and the mixture is stirred at room temperature and evacuated to -0.09 MPa for reaction for 1 hour to obtain component B.

[0158] (3) The above-mentioned component A and component B are mixed evenly in a volume ratio of 1:1 to obtain a two-component polyurethane structural adhesive.

[0159] In the above test, different weight portions of "rotaxane" structure were added to Example 1, Example 2 and Example 3 respectively, while no "rotaxane" structure was added to Comparative Example 1. In Comparative Example 2, in addition to no "rotaxane" structure being added to component A, 10 parts of plasticizer were additionally added to component B. In Comparative Example 3, in addition to no "rotaxane" structure being added to component A, 10 parts of difunctional modified castor oil were used in component A instead of multifunctional modified castor oil.

[0160] The two-component polyurethane structural adhesives prepared in the above-mentioned Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to various performance tests. The results are shown in Table 2.

[0161] Table 2 Performance data of Examples 1 to 3 and Comparative Examples 1 to 3

[0162] Performance Indicators Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Tensile shear strength (MPa, 25℃) 10.7 10.9 10.9 10.8 7.3 8.1 Tensile shear strength (MPa, 60℃) 5.9 6.5 6.4 6.3 4.1 4.8 Main tensile strength (MPa, 25℃) 11.0 10.9 11.4 11.5 7.9 8.5 Elongation at break (%, 25°C) 35 57 63 28 60 52 Main tensile strength (MPa, 60℃) 6.9 7.1 7.1 7.3 4.5 5.3 Elongation at break (%, 60℃) 62 89 99 49 105 97 Elastic modulus (MPa, 25℃) 680 670 700 730 490 530 Elastic modulus (MPa, 60℃) 85 79 87 89 52 61

[0163] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A high-elongation two-component polyurethane structural adhesive suitable for bonding power batteries, comprising component A and component B in a volume ratio of (0.8-1.2):1; The A component includes: 20-40 parts by weight of modified castor oil; 1 to 10 parts by weight of a small molecule diol chain extender; 1 to 10 parts by weight of "rotaxane" structure; 40-80 parts by weight of organic nitrogen and phosphorus polymer flame retardant filler; 0.5-5 parts by weight of white carbon black thixotropic agent; 0.3 to 3 parts by weight of silane coupling agent; 0.01 to 1 parts by weight of a metal catalyst; 0.1-2 parts by weight of blue color paste; The B component includes: 20-40 parts by weight of polymer polyisocyanate; 5 to 20 parts by weight of polyether diol; 40-80 parts by weight of organic nitrogen and phosphorus polymer flame retardant filler; 0.5 to 3 parts by weight of 4A molecular sieve water absorbent; 0.5-5 parts by weight of white carbon black thixotropic agent; 0.1-2 parts by weight of yellow color paste; The preparation method of the "rotaxane" structure is specifically as follows: Cyclodextrin and polyether diol are reacted in water at a molar equivalent ratio of (1 to 10):1, and then the water is removed and finally dried to obtain a "rotaxane" structure; the cyclodextrin is selected from one or more of α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin; and the average molecular weight of the polyether diol is 400 to 12000.

2. The high elongation two-component polyurethane structural adhesive suitable for bonding power batteries according to claim 1, characterized in that: The A component consists of the following components: 29-33 parts by weight of modified castor oil; 5 to 7 parts by weight of a small molecule diol chain extender; 2 to 6 parts by weight of "rotaxane" structure; 50-60 parts by weight of organic nitrogen and phosphorus polymer flame retardant filler; 1 to 3 parts by weight of white carbon black thixotropic agent; Silane coupling agent 0.5-1.5 parts by weight; 0.05-0.15 parts by weight of metal catalyst; 0.5-1.5 parts by weight of blue color paste.

3. The high elongation two-component polyurethane structural adhesive suitable for bonding power batteries according to claim 1, characterized in that: The B component consists of the following components: 25-35 parts by weight of polymer polyisocyanate; 8 to 12 parts by weight of polyether diol; 50-60 parts by weight of organic nitrogen and phosphorus polymer flame retardant filler; 1.5-2.5 parts by weight of 4A molecular sieve water absorbent; 1 to 3 parts by weight of white carbon black thixotropic agent; 0.5-1.5 parts by weight of yellow color paste.

4. The high elongation two-component polyurethane structural adhesive suitable for bonding power batteries according to claim 1, characterized in that: The reaction temperature is 20° C. to 30° C., the stirring speed is 100 rpm to 300 rpm, and the reaction time is 1 h to 4 h.

5. The high elongation two-component polyurethane structural adhesive suitable for bonding power batteries according to claim 1, characterized in that: The method for removing water is rotary evaporation; the vacuum degree of the rotary evaporation is ≤-0.09MPa, the temperature is 50°C to 70°C, and the rotation speed is 30rpm to 50rpm.

6. The high elongation two-component polyurethane structural adhesive suitable for bonding power batteries according to claim 1, characterized in that: The drying method is vacuum drying; the vacuum drying temperature is 70°C to 90°C, the vacuum degree is ≤-0.09MPa, and the drying time is 10h to 15h.

7. A method for preparing a high-elongation two-component polyurethane structural adhesive suitable for bonding power batteries according to any one of claims 1 to 6, comprising the following steps: a) The modified castor oil, small molecule diol chain extender, "rotaxane" structure, organic nitrogen and phosphorus polymer flame retardant filler, white carbon black thixotropic agent and silane coupling agent are heated to 110°C to 130°C under stirring, and dehydrated for 1.5h to 2.5h under vacuum ≤-0.09MPa, then cooled to ≤50°C, a metal catalyst and a blue color paste are added, and the vacuum is ≤-0.09MPa and the stirring is continued for 0.5h to 1h to obtain component A; b) stirring the polymer polyisocyanate and the polyether diol at 20° C. to 30° C. and evacuating to ≤-0.09 MPa for reaction for 1 h to 3 h, then adding organic nitrogen phosphorus polymer flame retardant filler, 4A molecular sieve dehydrating agent and white carbon black thixotropic agent, and then adding yellow color paste, stirring at 20° C. to 30° C. and evacuating to ≤-0.09 MPa for reaction for 0.5 h to 1.5 h to obtain component B; c) mixing the above-mentioned component A and component B in a volume ratio of (0.8-1.2):1 to obtain a high-elongation two-component polyurethane structural adhesive suitable for bonding power batteries; There is no restriction on the order of step a) and step b).

8. The preparation method according to claim 7, characterized in that: Before the organic nitrogen and phosphorus polymer flame retardant filler, 4A molecular sieve dehydrating agent and white carbon black thixotropic agent are added in step b), the method further comprises: The organic nitrogen and phosphorus polymer flame retardant filler, 4A molecular sieve water absorbent and white carbon black thixotropic agent are dried and dehydrated in a drying room at 90°C to 110°C for 20h to 30h.

Citation Information

Patent Citations

  • Adhesive composition, adhesive, and adhesive sheet

    CN103361003A

  • Thermoplastic elastomer composition, thermoplastic elastomer, and method for producing thermoplastic elastomer

    CN107109051A